PERBANDINGAN MODEL PEMBELAJARAN DISCOVERY BERBANTU PETA KONSEP DAN MODEL PEMBELAJARAN DISCOVERY TERHADAP PEMAHAMAN KONSEP MATERI PROTISTA SISWA KELAS X SMA NEGERI 1 SUKOHARJO TAHUN PELAJARAN 2014/2015 - Dedy Setiyawan; Meti Indrowati; Nurmiyati Nurmiyati (BIO-PEDAGOGI, 2016)
The research aims to determine the difference between Discovery  learning with concept map and Discovery learning to understanding the concept of  Protista  X Grade Students SMA Negeri 1 Sukoharjo the academic year 2014/2015. This research was quasi experiment research which used Posttest Only With Nonequivalent Control Group Design. The population studies are all X MIA class students of SMA Negeri 1 Sukoharjo in academic year 2014/2015. Sampling technique is using cluster sampling. There are two classes of the study sample, class as the experimental class 1 and the class as an experimental class 2. Class 2 experiments using Discovery  learning with concept map and experimental class 1 using  Discovery learning. The techique of collecting data is using Certain Response Index (CRI), observation sheets, and documentation. Hypothesis testing using t test assisted by SPSS 16. The result of this research is there a difference between Discovery  learning with concept map and  Discovery learning to  understanding of the concept of Protista X Grade Students SMA NEGERI  1 Sukoharjo the academic year 2014/2015.                                                                                                                                               Keywords: Discovery,Concept Map, Concept, Certain Response Index (CRI)